The Improvement of Semen Quality by Dietary Fiber Intake Is Positively Related With Gut Microbiota and SCFA in a Boar Model - Lin, Yan; Wang, Ke; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Li, Jian; Wu, Caimei; Zhang, Junjie; Xiong, Haoyu; Yu, Chenglong; et al. (Frontiers in Microbiology, 2022)
Fiber-rich diets have been positively associated with sperm quality; however, no study exists on the effects of dietary fiber and its metabolites on sperm quality in young or pre-pubescent animals. We aimed to explore the effect of dietary fiber supplementation on semen quality and its underlying mechanisms in the boar model. Sixty purebred Yorkshire weaning boars were randomly divided into four groups. T1, T2, and T3 had diets with different fiber levels, and T4 had a basal diet supplemented with butyrate and probiotics until the boars reached 160 days old. Thereafter, they were fed the same diet. The sperm motility and effective sperm number were significantly higher among T3 boars compared to T1 boars. Meanwhile, at 240 days of age, the acetic acid and total SCFAs in the sera of T3 and T4 boars were significantly higher than those in T1 boars. The microbiota abundance in T2 and T3 was significantly higher than that in T1 (P < 0.01). Dietary fiber sup-plementation increased “beneficial gut microbes” UCG-005, Rumenococcus, Rikenellaceae_RC9_gut_group, and Lactobacillus and decreased the relative abundance of “harmful microbes,” Clostridium_sensu_stricto_1, Romboutsia, and Turicibacter. Dietary fiber supplementation improves gut microbiota and promotes SCFA production, thereby enhancing spermatogenesis and semen quality. Moreover, the effect of dietary fiber is superior to that of its metabolites.